IL‐6 and IL‐8, secreted by myofibroblasts in the tumor microenvironment, activate HES1 to expand the cancer stem cell population in early colorectal tumor. Issue 3 (5th February 2021) - Kim, Bun; Seo, Yoojeong; Kwon, Ji‐Hee; Shin, Youmi; Kim, Suhyun; Park, Soo Jung; Park, Jae Jun; Cheon, Jae Hee; Kim, Won Ho; Il Kim, Tae
Abstract: Interaction between a tumor and its microenvironment is important for tumor initiation and progression. Cancer stem cells (CSCs) within the tumor interact with a microenvironmental niche that controls their maintenance and differentiation. We investigated the CSC‐promoting effect of factors released from myofibroblasts into the microenvironment of early colorectal cancer tumors and its molecular mechanism. By messenger RNA microarray analysis, expression of HES1, a Notch signaling target, significantly increased in Caco‐2 cells cocultured with 18Co cells (pericryptal myofibroblasts), compared to its expression in Caco‐2 cells cultured alone. Caco‐2 cells cultured in 18Co‐conditioned media (CM) showed a significant increase in CD133+CD44+ cells and HES1 expression compared to that in Caco‐2 cells cultured in regular media. Significant amounts of interleukin‐6 (IL‐6) and IL‐8 were detected in 18Co‐CM compared to levels in regular media. The 18Co‐CM‐induced increase in CD133+CD44+ cells was attenuated by IL‐6‐ and IL‐8‐neutralizing antibodies. Furthermore, these neutralizing antibodies and inhibitors of STAT3 and gamma‐secretase reduced the expression of HES1 induced in Caco‐2 cells cultured in 18Co‐CM. Immunohistochemical analysis of human tissues revealed that IL‐6, IL‐8, and HES1 expression increased from normal to adenoma, and from adenoma to cancer tissues. In addition, IL‐6 and HES1 expression was positively correlated in early colorectal cancer tissues. In conclusion, the increase of CSCs by myofibroblasts could be mediated by IL‐6/IL‐8‐induced HES1 activation in the tumor microenvironment. Based on these data, the IL‐6/IL‐8‐mediated Notch/HES1 and STAT3 pathway, through which CSCs interact with their microenvironment, might be a potential target for the prevention and treatment of colorectal tumors.